Zastosowanie LabVIEW do realizacji algorytmu wagowej synchronizacji danych pomiarowych = Using of LabVIEW for realizationthe weighted change algorithm of phase at synchronization of measuring data - Warda, Piotr (Zielona Góra: Uniwersytet Zielonogórski, Instytut Metrologii, Elektroniki i Informatyki)
The article presents the idea and implementation of an algorithm for weighted synchronization of data representing test and measured signal. Synchronized waveforms give the opportunity to compare instantaneous values, evaluate differences and determine an experimental error in information processing in the system. The LabVIEW environment was used for implementation. The application algorithm and examples of work results are presented.
Keywords: komputeryzacja; przyrządy pomiarowe; informatyka; technologie informacyjne